The development of the society and its relationship to the development of punishment in the UAE: Analytical theory study - Al-Zaabi, Omar Mohammed; Himat, Makia Gomaa Ahmed (Al-Adab Journal, 2021)
The security of society has been associated with the existence of deterrent punishment since ancient times, in order to achieve justice among the members of society and redress for the victim. The offender must be punished in the amount of harm caused by him with a view to reform and rehabilitation and not as revenge. No individual was born a criminal. However, the circumstances of socialization and the culture of the surrounding society are one of the most important aspects that affect the personality of the individual Punishment for the offender therefore plays a variety of roles in society. The punishment for the offender represented special deterrence aimed at rehabilitating the convicted person so that he could return to society by being affected and affected.The problem of considering that punishment is a double-edged sword that can maintain and stabilize society and reduce crime may be a weapon for society to use against itself Because of the importance of sanctions in society, this study will examine the stages of society's development and its relationship to the development of punishment in the UAE, trying to answer the question: How has society been developing in the UAE? What does this have to do with the development of punishment? To what extent have the forms of sanctions been associated with the development of UAE society?The importance of the study is that the subject of sanctions, as one of the main pillars for ensuring security and stability in society, is aimed at achieving deterrence (private and public), which is a prerequisite for social security and the fight against crime. With the development of the Penal Code and the pace with which the United Arab Emirates has followed modern penal policies, the United Arab Emirates has succeeded in applying penalties that are alternative to short-term custodial sentences, which have entailed many disadvantages for the convicted person, his family and society.